Snf2h-mediated chromatin organization and histone H1 dynamics govern cerebellar morphogenesis and neural maturation - Alvarez-Saavedra, Matías; De Repentigny, Yves; Lagali, Pamela S; Raghu Ram, Edupuganti V S; Yan, Keqin; Hashem, Emile; Ivanochko, Danton; Huh, Michael S; Yang, Doo; Mears, Alan J; Todd, Matthew A M; Corcoran, Chelsea P; et al. (Nature communications, 2014)
Chromatin compaction mediates progenitor to post-mitotic cell transitions and modulates gene expression programs, yet the mechanisms are poorly defined. Snf2h and Snf2l are ATP-dependent chromatin remodelling proteins that assemble, reposition and space nucleosomes, and are robustly expressed in the brain. Here we show that mice conditionally inactivated for Snf2h in neural progenitors have reduced levels of histone H1 and H2A variants that compromise chromatin fluidity and transcriptional programs within the developing cerebellum. Disorganized chromatin limits Purkinje and granule neuron progenitor expansion, resulting in abnormal post-natal foliation, while deregulated transcriptional programs contribute to altered neural maturation, motor dysfunction and death. However, mice survive to young adulthood, in part from Snf2l compensation that restores Engrailed-1 expression. Similarly, Purkinje-specific Snf2h ablation affects chromatin ultrastructure and dendritic arborization, but alters cognitive skills rather than motor control. Our studies reveal that Snf2h controls chromatin organization and histone H1 dynamics for the establishment of gene expression programs underlying cerebellar morphogenesis and neural maturation.
Keywords: galaktosidy; kvantitativní polymerázová řetězová reakce; indoly; Blotting, Western; chromozomální proteiny, nehistonové; Mice, Transgenic; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; Image Processing, Computer-Assisted; Analysis of Variance; Histones; restrukturace chromatinu; myši transgenní; toloniumchlorid; zvířata; metoda rotující tyčky; transmisní elektronová mikroskopie; Homeodomain Proteins; Indoles; Mice; Microarray Analysis; Rotarod Performance Test; Tolonium Chloride; Gene Expression Regulation, Developmental; mikročipová analýza; imunohistochemie; histony; koncové značení zlomů DNA in situ; mužské pohlaví; Purkyňovy buňky; Immunohistochemistry; adenosintrifosfatasy; Chromosomal Proteins, Non-Histone; Galactosides; vývojová regulace genové exprese; bromodeoxyuridin; polymerázová řetězová reakce s reverzní transkripcí; Neural Stem Cells; morfogeneze; fluorescence; Morphogenesis; homeodoménové proteiny; Microscopy, Electron, Transmission; Bromodeoxyuridine; Adenosine Triphosphatases; počítačové zpracování obrazu; Chromatin Immunoprecipitation; Cerebellum; analýza rozptylu; myši; In Situ Nick-End Labeling; ženské pohlaví; mozeček; Animals; Purkinje Cells; western blotting; chromatinová imunoprecipitace; hybridizace in situ; Fluorescence; Male; Chromatin Assembly and Disassembly; In Situ Hybridization; nervové kmenové buňky; Female